Growth of Services Management : A review - Sharma, Dr. N .R. (Innovative Research Thoughts, 2017)
A variety of management theories and research projects have investigated the interrelationships among companies, their workers, and the people who consume their services. There is a need for an integrated framework that includes important concepts, causal processes, and several levels of analysis in this body of work. Using Service Management, your organisation may get consistent, high-quality services. When it comes to IT governance, a proactive and strategic approach is used in which IT serves as an intermediate between service providers and important players in defining and encouraging corporate growth. When it comes down to it, service management may be described as a collection of organisational activities and duties aimed at providing high-value services to customers and users alike.